Pengaruh Kecanduan Smartphone Terhadap Prokrastinasi Akademik di SMA Negeri 8 Muaro Jambi - Indira Yuliansari; Rasimin Rasimin; Hera Wahyuni (Journal on Education, 2023)
This study aims to reveal how much influence smartphone addiction has on academic procrastination in class XI students at SMA Negeri 8 Muaro Jambi. Techniques in collecting data using a questionnaire. The population in this study were 73 students of class XI at SMP Negeri 8 Muaro Jambi. This type of research is quantitative research with an ex post facto approach. The results of the study generally show that students' smartphone addiction at SMA Negeri 8 Muaro Jambi as a whole is at a high level with a percentage of 66.31%. The results of the study also showed that there was a significant effect of smartphone addiction on academic procrastination at SMA Negeri 8 Muaro Jambi, which was 0.459 or 45.9% in the moderately strong classification with a determination of 0.17 – 0.49.